Keputusan Pembelian melalui Promosi Media Sosial dan Brand Image - Isnani, Nur Lailatul; Winata, A. Yahya Surya (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
In this study there are 3 variables, namely social media promotion, brand image, and purchase decision. This study uses quantitative methods with the number of respondents as many as 96 people. The purpose of this study was to determine the effect of sosial media promotion and brand image on purchasing decisions at Batik Mutiara Sendang Lamongan. The results of this study are (1) The promotion variable on sosial media has a positive and significant effect on purchasing decisions (2) The brand image variable has a positive and significant effect on purchasing  (3) Promotion variables on sosial media and brand image simultaneously influence purchasing decisions.